Design and Development of a Terrain Surveillance Carrier Bot Using a Microcontroller - T. Sriananda Ganesh (Journal of Power Electronics and Devices, 2023)
This work is an effort towards the development of a mobile robot that can be used to carry surveillance cameras over rough and uneven terrain. The design of the locomotion systems of mobile robots for unstructured environments is generally complex, particularly when they are required to move on uneven or soft terrains or to climb obstacles. This project sets out to analyze the state-of-the-art of locomotion mechanisms for ground mobile robots, focusing on solutions for unstructured environments, to help designers to select the optimal solution for specific operating requirements. Arduino Uno board with ATmega328 microcontroller is used as the brain of the system. The vehicle can be controlled using an android app. Obstacle-overcoming capability has been implemented by track belts and pully wheels. Moreover, it can run even after a flip of 180o which is achieved through the tilt sensor module. Hence, we can drive the vehicle without worrying about turning it upside down on an uneven surface. The connectivity between the mobile and the bot is done through Bluetooth. The implementation of this project can bring a great benefit to forest rangers and military soldiers working on the border. The developed system can be applied to military applications to protect people. The designed robot can cross any areas where not able to access by the soldiers. The sensors are highly sensitive to detect any movable objects within the boundary considered to sense the suspected items in the form of electrical signals. The speed of surveillance has been enhanced with the help of ATmega328.